Three-month Storage of Human Corneas in an Active Storage Machine. Issue 6 (June 2020) - Garcin, Thibaud; Gauthier, Anne-Sophie; Crouzet, Emmanuel; He, Zhiguo; Herbepin, Pascal; Perrache, Chantal; Acquart, Sophie; Cognasse, Fabrice; Forest, Fabien; Gain, Philippe; Thuret, Gilles
Abstract : Background: Corneal storage for the very long term, without degradation, would make it possible to optimize a very limited resource worldwide. We previously demonstrated the superiority, compared to conventional 4-week passive organ culture (OC), of an active storage machine (ASM) that restores intraocular pressure and medium renewal. Here, we investigate eye banking for up to 3 months. Methods: In a randomized preclinical trial with 24 paired corneas, 1 was stored in OC and the other in ASM, using the same medium. Assessments were done on the second day and at 3 months: endothelial cell density (ECD in cells/mm 2 ), corneal transparency and thickness. At day 86, OC corneas were deswelled in a common hyperosmotic medium, but not the ASM corneas, which had remained thin. In addition, at day 88, viable ECD was measured using a live/dead assay, and endothelial expression of Na + /K + ATPase, Cox IV, ZO-1, N-CAM, and CD166 was observed. Results: The ASM extended storage to 3 months with unprecedented endothelial cell quality: no OC corneas remained suitable for transplantation, but one-third of ASM corneas were compliant (ECD > 2000/mm 2 ). Given that corneas with ECD > 1600/mm 2 were also usable for emergency, 58% of ASM corneas were usable versus 33% in OC. EC survival was 53% higher in ASM ( P < 0.001), structural and functional proteins of ECs were much better preserved in ASM, and it prevented the constant major edema of OC. Conclusions: By extending graft survival to 3 months, the ASM will optimize eye banking and open up new perspectives in experimental research.